On the functions of toponyms in the memoir written by Julian Borzym, a nobleman from Podlasie - Jaros, Irena (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The aim of the paper is to indicate functions of toponyms in the text of the 19th century memoir written by Julian Borzym — a Polish nobleman coming from Podlasie (north-east part of Poland). Local and field names perform a informative function in the text. They create a geographical background for the presented events, show topography of towns and villages, indicate a position and status of described people (names of owned or leased properties). The informative function is connected with the locative one, that indicates the position of presented toponyms in time (e.g. names connected with historical events) and space, and also the affiliation to a given region which can be seen in the characteristic morphological features such as suffixes -(ow)izna/-yzna (Wierzbowizna, Piszczatowizna, Malinowszczyzna), -k instead of -ek in the forms of the genitive case (z Rzepk, z Rosk, do Niemierk, do Kobosk).